2018
DOI: 10.1080/1028415x.2018.1442184
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin B6 on dexamethasone-induced depression in mice model of despair

Abstract: Vitamin B6 prevented DEX-induced depression possibly by altering the GR function. Thus Vitamin B6 could be promising in patients suffering from GC-induced psychiatric adverse effects and probably controlling stress and preventing its affective disorder out comes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Pyridoxamine, one form of vitamin B6, is important for synthesis of many neurotransmitters such as GABA, serotonin, dopamine, noradrenaline, histamine, glycine, and d-serine, and currently used as therapeutics for autism 30 . It also has been reported that vitamin B6 administration attenuates depression-like behaviors in dexamethasone-induced depression model mice 31 . In addition, β-alanine administration has been reported to improve behaviors of depression in post-traumatic stress disorder (PTSD) model mice by increasing carnosine levels in the brain and maintaining hippocampal BDNF expression, an important target of antidepressants 32 , 33 .…”
Section: Discussionmentioning
confidence: 93%
“…Pyridoxamine, one form of vitamin B6, is important for synthesis of many neurotransmitters such as GABA, serotonin, dopamine, noradrenaline, histamine, glycine, and d-serine, and currently used as therapeutics for autism 30 . It also has been reported that vitamin B6 administration attenuates depression-like behaviors in dexamethasone-induced depression model mice 31 . In addition, β-alanine administration has been reported to improve behaviors of depression in post-traumatic stress disorder (PTSD) model mice by increasing carnosine levels in the brain and maintaining hippocampal BDNF expression, an important target of antidepressants 32 , 33 .…”
Section: Discussionmentioning
confidence: 93%
“…This was proven earlier since it was shown that Dex dose dependently increased the immobility time during the FST. 20 By adding the Syn mixture the immobility time in the FST was reduced not only when Dex was injected as single dose but also when it was administered for seven days. This showed that Syn mixture could have preventive effects on Dex induced mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…19 Furthermore, administration of dexamethasone (Dex) and corticosterone have produced depression-like behaviors in animal models. 20,21 Previously the antidepressant effects of a synbiotic (Syn; probiotic + prebiotic) mixture was proved in animal model of depression. 22 The mixture was chosen on the basis that Lactobacilli and Bifidobacteria have antidepressant effects in animal studies thus a manufactured premixed product was chosen that comprised these genus and also a prebiotic, fructo-oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…The model was established based on previous glucocorticoid‐induced depression (Kv et al, ; Mesripour, Alhimma, & Hajhashemi, ) and had been slightly modified. Sixty mice were randomly divided into control and CORT groups.…”
Section: Methodsmentioning
confidence: 99%